ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DITINJAU DARI ASPEK PERENCANAAN GURU DALAM MENYUSUN MODUL AJAR DI SDIT AL HIJRAH 2 DELI SERDANG - Andriani, Eva; Simanjuntak, Sorta; Simanungkalit, Erlinda; Ananda, Lala Jelita; Purnomo, Try Wahyu (Jurnal Merah Putih Sekolah Dasar, 2024)
This research is motivated by the change in curriculum from K13 to Merdeka Curriculum, especially in changing the lesson plan learning tools to Teaching Modules. Therefore, the purpose of this study is to determine the implementation of the independent curriculum in terms of teacher planning in preparing teaching modules at SDIT Al Hijrah 2 Deli Serdang. This research is a descriptive qualitative research. The subjects of this research are the principal, grade I teacher and grade V teacher. While the object of research is teacher planning in preparing teaching modules for the independent curriculum. Data collection was carried out by observation, interview, and documentation. The results of this study indicate that teacher planning for teaching modules is carried out in stages, 1) teachers are given training by the school, 2) teachers discuss and learn together with other teachers at school or in KKG. The obstacles faced by teachers in designing teaching modules, namely teachers are constrained in time, teachers are confused in determining learning methods, and teachers must adjust to the phase of learner development. To overcome these obstacles, the school again provides guidance and training to teachers to be able to plan the preparation of teaching modules appropriately.Keywords: Teacher Planning, Teaching Modules, Independent Curriculum.